Clinical observation on application of Jiao Tai Pill on Shenque (CV 8) in treating insomnia - Li, Yong (Journal of acupuncture and tuina science, 2010)
Objective To observe the clinical efficacy of application of Jiao Tai Pill on acupoint Shenque (CV 8) in the treatment of insomnia. Methods A total of 152 subjects were randomized in visit sequence into two groups: a treatment group in which 76 cases were treated by application of Jiao Tai Pill on point Shenque (CV 8) and a control group in which 76 cases were treated by oral administration of Jiao Tai Pill , both with a course of four weeks. Pittsburgh Sleep Quality Index (PSQI) was used to evaluate the clinical efficacy respectively before treatment, at one-week, two-week and four-week treatment, and one week, two weeks and four weeks after treatment. Results After four-week treatment, the sleep quality had improved in both groups, with no statistical difference between the two groups; there was no side-effect and the sleep quality kept improving thereafter. Conclusion Application of Jiao Tai Pill on point Shenque (CV 8) and oral administration of Jiao Tai Pill both have positive effects on insomnia and no apparent withdrawal reaction after treatment.